Español: comencemos - Schmitt, Conrad J.; Hearne, Jack (New York, Webster Division, McGraw-Hill, 1974)
A basic Spanish text for junior high school students including vocabulary, grammatical structure, dialog, cultural readings, and written exercises.
Part of an audio-lingual-visual program which consists of a student text, teacher's edition, workbook, tapes, tests, and visual aids.
Keywords: Spanish language -- Textbooks for foreign speakers -- English; Spanish language -- Grammar